Leo Baeck's “Individuum Ineffabile” - Ellenson, David Harry 1947-; Mendes Flor, Paul 1941-2024 (2021)
Rabbi Leo Baeck (1873-1956) has long been recognized as a man of extraordinary achievement. The last head of Hochschule für die Wissenschaft des Judentums, the Liberal rabbinical seminary that continued until 1942 to ordain rabbis for a European Jewish community on the eve of destruction, Baeck, a scholar, philosopher, and theologian, also served as head of the German Jewish community during the darkest years of Nazi rule. Though Baeck had many critics, his prominence and the respect he garnered from every sector of German Jewry cannot be gainsaid. As his biographer, translator, and student Albert H. Friedlander observed, “The leaders of a community, more often than not, are chosen for the success they have obtained in the market place, for the so-called 'practicality’ that men can understand.” However, when the German Jewish community was called upon to choose its leader during the horrific Hitler years, “They chose their greatest rabbi. They felt that this time of need required a man who drew his full strength out of his living belief in God, out of his impassioned love for the Jewish people.”